Health Belief Model pada Kepatuhan Hand Hygiene di Bangsal Berisiko Tinggi Healthcare Acquired Infections (HAIs) (Studi Kasus Pada Rumah Sakit X) - Merita Arini (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2016)
as a global problem, patient morbidity and mortality in hospital caused by Healthcare Acquired Infections (HAIs) can be prevented by implementation of Hand Hygiene (HH). This research aims to know the influence of Health Belief Model variables to HH compliance. there was a quantitative study by survey approach and cross-sectional design. The population consisted all of nurses in high risk HAIs ward (ICU and surgical ward, 30 respondents). HCW’s perceptions were measured through self-administered questioner. The compliance of HCWs was measured by observation form of HH. compliance rate of HH based on moment was 46,29 %. Compliance of ICU nurses where higer than surgery ward nurses. Only workplace variable that had significant influence HH compliance (p=0,000). Perception variables can not used as predictor to HH compliance. HH compliance should be increase. Workplace factor had significant influence to HH compliance.